(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
Technology is an integral part of everyday life, and its utilisation significantly influences how buyers behave when making decisions on their purchases, no matter the type of goods purchased. Therefore, it is necessary to observe how various generations of shoppers, based on technological solutions, change their shopping behaviour for different groups of products. This paper is focused on the online aspect of non-luxurious apparel shopping. Two groups of online retailers are researched: pure-play e-retailers and omnichannel retailers. The study adopted an exploratory approach, and the data were collected using semi-structured interviews among young females. In this study, we addressed and answered three research questions. The first question focused on the choice of type of online retailer - e-retailer or omnichannel. The second question was oriented to constructs of the UTAUT2 model and their relevance among young females regarding apparel shopping. The third question highlights the perspective of sustainability and environmental concerns when buying apparel online.